2013
DOI: 10.1136/bmjopen-2013-002771
|View full text |Cite
|
Sign up to set email alerts
|

Results from the Upper Limb International Spasticity Study-II (ULIS-II): a large, international, prospective cohort study investigating practice and goal attainment following treatment with botulinum toxin A in real-life clinical management

Abstract: ObjectiveTo describe real-life practice and person-centred outcomes in the treatment of poststroke upper limb spasticity with botulinum toxin A (BoNT-A).DesignObservational, prospective study.Setting84 secondary care centres in 22 countries.Participants456 adults (≥18 years) with poststroke upper limb spasticity treated with one cycle of BoNT-A.Methods/outcomesMuscle selection, BoNT-A preparation, injection technique and timing of follow-up were conducted according to routine practice for each centre. Primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
77
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 32 publications
14
77
1
3
Order By: Relevance
“…Originally described by Kiresuk and Sherman (1968) in the 1960s, goal attainment scaling has been used in many areas of practice that warrant an individualized approach to outcome evaluation including rehabilitation (Hurn et al, 2006;Turner-Stokes et al, 2009a). It is increasingly used as a person-centred outcome measure in research evaluations of outcome following spasticity intervention (Ashford and Turner-Stokes, 2006;McCrory et al, 2009;Borg et al, 2011;Turner-Stokes et al, 2013;Turner-Stokes et al, 2013) and is recommended as a method of recording patient-reported outcomes in guidelines for management of spasticity with botulinum toxin (Royal College Of Physicians, British Society Of Rehabilitation Medicine, Chartered Society Of Physiotherapy, and Association Of Chartered Physiotherapist Interested In Neurology, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally described by Kiresuk and Sherman (1968) in the 1960s, goal attainment scaling has been used in many areas of practice that warrant an individualized approach to outcome evaluation including rehabilitation (Hurn et al, 2006;Turner-Stokes et al, 2009a). It is increasingly used as a person-centred outcome measure in research evaluations of outcome following spasticity intervention (Ashford and Turner-Stokes, 2006;McCrory et al, 2009;Borg et al, 2011;Turner-Stokes et al, 2013;Turner-Stokes et al, 2013) and is recommended as a method of recording patient-reported outcomes in guidelines for management of spasticity with botulinum toxin (Royal College Of Physicians, British Society Of Rehabilitation Medicine, Chartered Society Of Physiotherapy, and Association Of Chartered Physiotherapist Interested In Neurology, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…It is increasingly used as a person-centred outcome measure in research evaluations of outcome following spasticity intervention [16][17][18][19][20] , and is recommended as a method of recording patient-reported outcomes in guidelines for management of spasticity with Botulinum toxin 21 .…”
Section: Procedurementioning
confidence: 99%
“…Учитывая большую когорту пациентов, проанализированную в международном исследовании ULIS-II, имеющиеся различия в методах лечения спастичности на фоне максимально персонифицированного подхода в оценке клинических результатов с помощью использования шкалы GAS, особый интерес для российских специалистов, занимающихся ботулинотерапией в лечении спастичности после инсульта, представляют результаты анализа данных российской группы пациентов. Целью данного анализа является сравнение данных российской подгруппы пациентов и ранее опубликованных результатов анализа общей популяции пациентов [21].…”
Section: лечение нервных и психических заболеванийunclassified
“…В российскую подгруппу были включены 26 (63,4%) мужчин и 15 (36,6%) женщин, средний возраст -53,9 года (от 28 до 76 лет). Демографические показатели российской подгруппы сходны с ранее опубликованными показателями международной популяции [21] (табл. 1).…”
Section: материал и методыunclassified
“…Other goals relate to increasing a person’s ability to perform activities and participate in their life situation [6, 11, 16, 1820]. To date, no systematic review has done this.…”
Section: Introductionmentioning
confidence: 99%